Odpowiedź :
Zad. 2
a) y - 3
b) x · 6
c) p · 2
d) y : 3
Zad. 3
7 - 2 · 2 = 7 - 4 = 3
Odp. B
Zad. 4
2a + 7a = 9a
2x - 4x = -2x
6y + y - 3y = 7y - 3y = 4y
Zad. 5
4x - 2 + 5x - 10x = -x - 2 (nie jestem pewna)
3a + 8 - 12a + 9 = -9a + 17
Zad. 6
9 · 6 + 4 = 54 + 4 = 58
7 · (-3) + 10 = -21 + 10 = -11
Mam nadzieję, że pomogłam. Liczę na naj.
Odpowiedź:
Zad. 1
Odp. A
Zad. 2
a) y - 3
b) 6x
c) p + 2
d) y : 3
Zad. 3
7 - 2x
Dla x = 2
7 - (2*2)
7 - 4 = 3
Zad. 4
2a + 7a = 9a
2x - 4x = - 2x
6y + y - 3y = 7y - 3y = 4y
Zad. 5
4x - 2 + 5x - 10x
4x + 5x - 10x - 2
9x - 10x - 2
-x - 2
3a + 8 - 12a + 9
3a - 12a + 8 + 9
- 9a + 17
Zad. 6
Dla x = 6
9x + 4
(9*6) + 4
56 + 4 = 60
Dla y = (-3)
7y + 10
{7*(-3)} + 10
- 21 + 10 = - 11
Szczegółowe wyjaśnienie:
Pozdrawiam :)